2022
DOI: 10.1111/den.14397
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and technical outcomes of endoscopic closure of postendoscopic submucosal dissection defects: Literature review over one decade

Abstract: Endoscopic submucosal dissection (ESD), which enables curative en bloc resection of early gastrointestinal neoplasms, has been an attractive minimally invasive surgery during the past two decades. Large post‐ESD defects must be carefully managed to prevent adverse events (AEs). The major AEs comprise delayed bleeding (DB) and delayed perforation (DP), and overall AEs comprise DB plus DP. This review aimed to clarify the clinical efficacy and technical outcomes of endoscopic prophylactic closure for post‐ESD de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 93 publications
(311 reference statements)
1
16
0
Order By: Relevance
“…With the development of ESD and EFTR, it has become possible to resect lesions en bloc. Postoperative adverse events can be prevented using clips and special devices for the closure of post‐ER mucosal and full‐thickness defects 125 . Researchers have gradually solved several problems associated with clip closure, including the reliability of methods, limitations on defect size, endoscopic maneuverability, cost‐effectiveness, and closure durability.…”
Section: Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…With the development of ESD and EFTR, it has become possible to resect lesions en bloc. Postoperative adverse events can be prevented using clips and special devices for the closure of post‐ER mucosal and full‐thickness defects 125 . Researchers have gradually solved several problems associated with clip closure, including the reliability of methods, limitations on defect size, endoscopic maneuverability, cost‐effectiveness, and closure durability.…”
Section: Future Perspectivementioning
confidence: 99%
“…Postoperative adverse events can be prevented using clips and special devices for the closure of post-ER mucosal and full-thickness defects. 125 Researchers have gradually solved several problems associated with clip closure, including the reliability of methods, limitations on defect size, endoscopic maneuverability, cost-effectiveness, and closure durability. The rates of postoperative adverse events after ER have also been clarified for patients with different background risks.…”
Section: Full-thickness Defect Closure Using Clips and Special Devicesmentioning
confidence: 99%
“…Closure of mucosal defects after endoscopic mucosal resection or endoscopic submucosal dissection (ESD) has been shown to reduce the risk of delayed bleeding and perforation 1 2 3 4 . Defect closure can be achieved using over-the-scope (OTS) clips, through-the-scope (TTS) clips, or endoscopic suturing 4 .…”
Section: Figmentioning
confidence: 99%
“…Endoscopic resection of SDETs has a high AE risk owing to the thin duodenal wall and the exposure of pancreatic proteolytic enzymes to the wound 5 . Recently, reports have indicated that using several prophylactic closures and an endoscopic tissue shielding method for ER defects decreases the delayed AE risk 6–13 . However, AEs occurring after duodenal ER have a high surgical conversion risk, with reported rates of 3.5–66.7%, 0%, and 33.3–100% for intraoperative perforation, delayed bleeding, and delayed perforation after ESD, respectively, in Japan and East Asia 2,6–10,14–22 .…”
Section: Introductionmentioning
confidence: 99%